A study on the inspiration of Japan's football youth training model on the cultivation of school football reserves in China - Chen, Qiuyi; Jiang, Bo; Chen, Zhijun; Deng, Wenquan; Wang, Shaojie (Quality in Sport, 2024)
This article mainly introduces the Japanese football youth training model and its inspiration to the cultivation of school football reserves in China. The article firstly outlines the development history, system structure and core concept of Japanese football youth training, pointing out its focus on basic training, team spirit and the pursuit of excellence. Then, the article analyses the current situation and problems in the training of school football reserves in China, including the training mode, selection mechanism and training and competition system. Afterwards, the article focuses on the inspiration of the Japanese football youth training model to China's school football, and proposes to optimise the conceptual change, system construction, coach training and tournament organisation, etc. The article also describes in detail the current situation and problems of school football reserve talents training in China. The article also elaborates on the optimisation strategies for the cultivation of reserve talents in China's school football, including policy support, education and teaching reform, social force participation and international exchanges. Finally, the article points out that by learning from the successful experience of Japan's football youth training model, it can promote the level of China's school football reserve training and lay a solid foundation for the development of a strong sports country.